2011
DOI: 10.1007/s00228-011-1150-0
|View full text |Cite
|
Sign up to set email alerts
|

The interactions of age, sex, body mass index, genetics, and steroid weight-based doses on tacrolimus dosing requirement after adult kidney transplantation

Abstract: Our results demonstrate the importance of the interaction among genetic and clinical factors in conditioning tacrolimus disposition, with corticosteroid weight-based dose being the only modifiable risk factor for tacrolimus requirement. As the tacrolimus dosing requirement increases with increasing tacrolimus clearance through concomitant steroid use, undesirable changes in tacrolimus levels may occur when steroid doses are tapered, predominantly in slow metabolizers. This often neglected drug interaction has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
78
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 54 publications
11
78
2
2
Order By: Relevance
“…[2629] Age was also identified as a covariate for CL/F and the model demonstrated that the apparent clearance of tacrolimus decreases with age. Older age is reported to be associated with higher tacrolimus dose-normalized concentration or lower tacrolimus dose requirement, [3032] which is in accordance with our finding. Diabetes significantly reduced the objective function by 12.96 as a covariate for an absorption lag time.…”
Section: Discussionsupporting
confidence: 92%
“…[2629] Age was also identified as a covariate for CL/F and the model demonstrated that the apparent clearance of tacrolimus decreases with age. Older age is reported to be associated with higher tacrolimus dose-normalized concentration or lower tacrolimus dose requirement, [3032] which is in accordance with our finding. Diabetes significantly reduced the objective function by 12.96 as a covariate for an absorption lag time.…”
Section: Discussionsupporting
confidence: 92%
“…This is of note because younger age is associated with faster Tac metabolism20. Other risk factors for BKV infection like male gender219, Caucasian race221 and diabetes mellitus21 which have been reported could not be confirmed in our study.…”
Section: Discussioncontrasting
confidence: 59%
“…Using 450 transplant recipients, Stratta et al showed that the metabolism of tacrolimus was slower in men than in women and suggested that the dose of tacrolimus should be adjusted based on sex (Stratta et al 2011). …”
Section: Discussionmentioning
confidence: 99%